Obteniendo los coeficientes de restitución y arrastre en un solo experimento - Pavioni, O.D.; Ortega, F.M. (Revista Mexicana de Física E, 2015)
In this paper is shown a simple and novel way of finding the coefficient of restitution for the collision between a ball and the floor, where also the drag coefficient of a spherical shape is obtained.